PATH-16. MOLECULAR PATHOLOGY AND CLINICAL CHARACTERISTICS OF MMR DEFICIENCY (MMRd) IN DIFFUSE GLIOMAS. (5th November 2018) - Touat, Mehdi; Santagata, Sandro; Guillerm, Erell; Bi, Wenya; Beuvon, Frédéric; Mokhtari, Karima; Giry, Marine; Guegan, Justine; Block, Shannon; Carpentier, Alexandre; Delattre, Jean-Yves; Sanson, Marc; et al.
Abstract: BACKGROUND: MMR deficiency (MMRd) is found in a subset of gliomas. Emerging evidence indicates that MMRd could serve as predictive biomarker for both response to immunotherapy and resistance to alkylating agents. However, the molecular epidemiology, outcome, and the optimal diagnostic method of MMRd are poorly defined in gliomas. METHODS: A cohort of 350 adult gliomas was characterized as to WHO 2016 diagnosis, IDH1/2 sequencing, MGMT promoter methylation, prior treatment and outcome. Immunohistochemistry of MMR proteins (MSH2, MSH6, MLH1, PMS2) was performed in 260 tumors with available tissue. 100 tumors were analyzed with next generation targeted exome sequencing (NGS, Oncopanel) of 447 cancer genes, including full exon coverage of MMR genes. Comparisons between results from IHC, NGS and microsatellite instability (MSI) testing using pentaplex PCR amplification testing were incorporated to inform best practices. RESULTS: 53/260 tumors showed immunohistochemical (ie MMR protein staining loss) and/or molecular (ie presence of MMR pathogenic mutation with hypermutation) evidence of MMRd. No MSI was found by pentaplex PCR. 38/260 tumors harbored loss of protein expression of one or two MMR proteins: 15 showed loss of MSH6 protein (with/without concomitant MSH2 loss) and 23 had loss of PMS2 (with/without MLH1 loss). Analysis of 201 consecutive recurrent tumors from alkylator pre-treated patients showed significant association between MMRd and the presence of IDH1/2 mutation: MMRd in 20/90 (22.2%) of IDH1/2-mutant tumors vs 2/111 (1.8%) of IDH1/2-wild-type tumors (p<4.10–6). In addition, MMRd was found in 6/17 (35%) of patients with de novo gliomas and clinical features indicating possible inherited MMRd. Outcomes and updated results of molecular biomarker analyses will be presented at the conference. CONCLUSIONS: Loss of MMR protein expression by IHC is significantly associated with IDH-mutant relapses and a clinico-histo-molecular presentation suggestive of germline MMRd. NGS and IHC of MMR proteins are highly concordant in gliomas, while MSI testing lacks sensitivity.